Indications Resignifying old practices: non agricultural practices as surviving strategies in the case of Santa Maria do Suaçuí MG. - Jane Ferreira de Sousa (2006)
lt;p align="justify"gt; The modernization of the agriculture is founded on the logic that presupposed an identity between agriculture development and rural development. Where these policies had been implemented, it has been proved that while agriculture modernized, rural poverty persisted and grew, still where it occurred, the familiar agriculturists were excluded from the markets. This allows us to justify that the parameters of rural development surpass the agriculture sphere. This research analyses the strategies of reproduction of familiar farms of the municipality of Santa Maria do Suaçuí, which has passed through a long period of economic stagnation, showing an under-developed agriculture excluded from the technological development. This process generates new techno productive dynamics causing strong impacts on rural development. On one hand, many producers have abandoned the agricultural business freeing family labor force from farming activities. On the other side, there is growing numbers of agriculturists, and their families, who no longer run activities related to agricultural business. In this process it has appeared the pluriactive family, which combines the agricultural activities with the non agricultural businesses, inside and outside the farm. This is a case study of the family farms of Santa Maria do Suaçuí, a municipality that has gone through economic hardship still produces and survives. It was learned that the familiar agriculturists of Santa Maria do Suaçuí established a system of production based in cooperation with each other, characterized by the existing relations of reciprocity e solidarity in community lives. From then on, many agriculturists have become to carry on a variety of different activities, not all directly linked with agricultural. Poultry, milk and vegetables productions are the main strategies of reproduction linked to agriculture. Agroindustrialization and services have also increased. This development of new activities provoke social differentiation, however, the mercantilism didnt imply the proletarianisation of agriculturists, but causes the appearance of new social reproduction strategies. Therefore, it is believed that the main contribution of this study to the familiar agriculture is the analysis of surviving alternatives for familiar agriculturists in economic stagnated areas.lt;/pgt;